Water Quality Analysis in Vaname Shrimp Cultivation at PT Tanjung Berlian Biru, Sumbawa, West Nusa Tenggara - Ulfa, Mariya; Ahdiansyah, Yudi; Mardhia, Dwi; Kautsari, Neri; Bahri, Syamsul (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
Water quality checks in vaname shrimp cultivation activities are very important to maintain the condition and performance of the shrimp being cultivated. Consistent water quality monitoring based on water quality standards will ensure that whiteleg shrimp are in optimal condition, thereby increasing harvest production yields. This study aims to analyze the water quality parameter measurements in whiteleg shrimp cultivation at PT. Tanjung Berlian Biru, Sumbawa, West Nusa Tenggara. The method used is a survey method with quantitative descriptive data analysis. Measurement of water quality parameters was carried out in two pond plots, namely plots B5 and B6, with the parameters observed including temperature, pH, salinity, dissolved oxygen (DO), Total Organic Meter (TOM), alkalinity and ammonium. The results showed that the temperature ranged between 27.1°C–31.1°C (B5) and 26.8°C–30.9°C (B6). Salinity in both plots was uniform, namely 28–35 ppt. DO ranged between 3.87–5.27 mg/l (B5) and 4.13–5.33 mg/l (B6). pH was in the range of 7.6–8.4 (B5) and 7.6–8.2 (B6). Alkalinity ranged between 119–187 ppm (B5) and 128–204 ppm (B6). NH₄ in both plots was in the range of 0–3.0 ppm, while TOM ranged from 109–117 mg/l (B5) and 113–118 mg/l (B6). These parameters reflect environmental conditions that support the growth of whiteleg shrimp.